Degradation of pharmaceutical compound pentoxifylline in water by non-thermal plasma treatment - Magureanu, Monica; Piroi, Daniela; Mandache, Nicolae Bogdan; David, Victor; Medvedovici, Andrei; Parvulescu, Vasile I. (Water research (Oxford), 2010)
The decomposition of a model pharmaceutical compound, pentoxifylline, in aqueous solution was investigated using a dielectric barrier discharge (DBD) in coaxial configuration, operated in pulsed regime, at atmospheric pressure and room temperature. The solution was made to flow as a film over the surface of the inner electrode of the plasma reactor, so the discharge was generated at the gas–liquid interface. Oxygen was introduced with a flow rate of 600 sccm. After 60 min plasma treatment 92.5% removal of pentoxifylline was achieved and the corresponding decomposition yield was 16 g/kWh. It was found that pentoxifylline degradation depended on the initial concentration of the compound, being faster for lower concentrations. Faster decomposition of pentoxifylline could be also achieved by increasing the pulse repetition rate, and implicitly the power introduced in the discharge, however, this had little effect on the decomposition yield. The degradation products were investigated by liquid chromatography–mass spectrometry technique (LC–MS). The evolution of the intermediates during plasma treatment showed a fast increase in the first 30 min, followed by a slower decrease, so that these products are almost completely removed after 120 min treatment time.